Pendampingan UMKM Keripik Sale Pisang Kering Surya dalam pengembangan produksi guna meningkatkan kualitas produk - Devi Rahmasari; Randita Kusuma Pramudya Cahyani; Reiza Pratama; Edi Sumantri; Tri Esti Masita (Nur Science Institute, 2026)
MSMEs Dried Banana Sale Chips Surya is one business actor with growth potential, but still faces various obstacles in the production process. The main problems include limited production facilities, traditional product cooling processes, and suboptimal packaging quality, which affect production efficiency and product shelf life. This service activity aims to improve product quality and production process efficiency by providing grants for supporting equipment, including plastic silencer machines and fan blowers. The implementation method uses a participatory approach, including observation, brainstorming, technology application, mentoring, and evaluation. The results of the activity show that the use of plastic siler machines can improve the quality and safety of product packaging, extend shelf life, and increase selling value. Meanwhile, the use of fan blowers speeds up the cooling of banana chips, making production more efficient. Thus, the application of appropriate technology through production equipment grants has been proven to improve product quality and production efficiency for MSMEs in the Dried Banana Sale Chips sector.